1994
DOI: 10.1007/bf02444119
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of adaptation to hypoxia and its prolongation by pharmacological agents in rats prone to audiogenic epilepsy

Abstract: Cytophotometric determination of RNA in various brain structures of hypoxia-adapted and unadapted epilepsy-prone rats at different times after an epileptic seizure shows much smaller decreases in RNA levels and their much more rapid return to normal in the adapted than in the unadapted rats. The adaptation to hypoxia produces a marked anticonvulsive effect, and this effect is enhanced and prolonged considerably by pharmacotherapy.Key Words: adaptation to hypoxia; audiogenic epilepsy; therapy Adaptation to peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…196 Various antistress effects of IHT have been described by IHT pioneer Felix Meerson. 179 He and his co-workers found that IHT prevented stomach ulcers induced by restraint stress and behavioral disorders in rats. 197 Zhu et al 198 reported that IHT produced antidepressant-like effects in rats subjected to a variety of mild stressors, e.g.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
See 2 more Smart Citations
“…196 Various antistress effects of IHT have been described by IHT pioneer Felix Meerson. 179 He and his co-workers found that IHT prevented stomach ulcers induced by restraint stress and behavioral disorders in rats. 197 Zhu et al 198 reported that IHT produced antidepressant-like effects in rats subjected to a variety of mild stressors, e.g.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
“…In addition to its direct effects on cerebrovascular function, IHT has been employed to effectively treat conditions associated with VRF, including systemic hypertension, atherogenic changes in the lipid profile, smoking, obesity and metabolic syndrome, ischemic cardiac disease, and psychological stress. 101,102,179,180 While not specifically focused on VRF, a recent review by Navarrete-Opazo and Mitchell 181 described IHT's effects on the respiratory, cardiovascular, immune, metabolic, skeletal, and nervous systems. The following discussion extends that of Navarrete-Opazo and Mitchell 181 to more specifically address IHT's impact on VRF.…”
Section: Intermittent Hypoxic Training (Iht) Improves Cerebrovascularmentioning
confidence: 99%
See 1 more Smart Citation
“…1), while the activity of catalase decreased 22%. In this case, a decrease in enzyme activity does not indicate an adaptive modification in response to a decrease in the intensity of LPO, as, occurs, for example, at a lowered partial pressure [14], but, on the contrary, points to excessive activation of LPO [5] and a considerable accumulation of hydrogen peroxide. Since LPO is confined to the membrane and the efficiency of Ca transport correlates with the intensity of LPO [2], such a decrease in the activity of catalase can be expected to impair the function of the SPR Ca-transporting system.…”
Section: Resultsmentioning
confidence: 99%
“…Adaptation to a short-term stress, which can prevent disturbances of the electrical stability of the heart and arrhythmias in stress, ischemia, reperfusion, myocardial infarction, and postinfarction cardiosclerosis [14], is an example of combined activation of the central and peripheral stresslimiting systems of the organism. Adaptation to stress also prevents stress-induced damage to the Na,K pump [6] and optimizes the function of the Ca pump [13], i.e., it triggers a mechanism that operates at the level of the heart, limits arrhythmias, and protects against alterations in Ca homeostasis.…”
mentioning
confidence: 99%